Baicalin-modified polyethylenimine for miR-34a efficient and safe delivery - Yingying Wang; Yingying Wang; Baiyan Wang; Yangfan Xiao; Qingchun Cai; Junyue Xing; Hao Tang; Ruiqin Li; Hongtao Zhang; Hongtao Zhang; Hongtao Zhang; Hongtao Zhang (Frontiers in Bioengineering and Biotechnology)
The security and efficiency of gene delivery vectors are inseparable for the successful construction of a gene delivery vector. This work provides a practical method to construct a charge-regulated, hydrophobic-modified, and functionally modified polyethylenimine (PEI) with effective gene delivery and perfect transfection performance through a condensation reaction, named BA-PEI. The carrier was shown to possess a favorable compaction of miRNAs into positively charged nanoparticles with a hydrodynamic size of approximately 100 nm. Additionally, BA-PEI possesses perfect degradability, which benefits the release of miR-34a from the complexes. In A549 cells, the expression level of the miR-34a gene was checked by Western blotting, which reflects the transfection efficiency of BA-PEI/miR-34a. When miR-34a is delivered to the cell, the perfect anti-tumor ability of the BA-PEI/miR-34a complex was systematically evaluated with the suppressor tumor gene miR-34a system in vitro and in vivo. BA-PEI-mediated miR-34a gene transfection is more secure and effective than the commercial transfection reagent, thus providing a novel approach for miR-34a-based gene therapy.